2018
DOI: 10.1016/j.nbd.2017.12.015
|View full text |Cite
|
Sign up to set email alerts
|

Effect of early embryonic deletion of huntingtin from pyramidal neurons on the development and long-term survival of neurons in cerebral cortex and striatum

Abstract: We evaluated the impact of early embryonic deletion of huntingtin (htt) from pyramidal neurons on cortical development, cortical neuron survival and motor behavior, using a cre-loxP strategy to inactivate the mouse htt gene (Hdh) in emx1-expressing cell lineages. Western blot confirmed substantial htt reduction in cerebral cortex of these Emx-httKO mice, with residual cortical htt in all likelihood restricted to cortical interneurons of the subpallial lineage and/or vascular endothelial cells. Despite the loss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
18
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 123 publications
(159 reference statements)
2
18
0
Order By: Relevance
“…Our previous studies have shown that pan-neural loss of Htt function during the murine developmental period leads to motor deficits and hyperkinetic phenotypes expressed during adult life (Arteaga-Bracho et al, 2016). Consistent with our findings, a more recent study reported that deletion of Htt in pallial lineages also results in hyperactivity and motor deficits (Dragatsis et al, 2018). To define whether the selective loss of Htt function in subpallial-derived lineages contribute to HD-like motor abnormalities, we examined motor coordination and free locomotion using the balance beam, rotarod and the open-field tests, respectively.…”
Section: Ablation Of Huntingtin In the Gsx2 And Nkx21 Lineages Resulsupporting
confidence: 92%
“…Our previous studies have shown that pan-neural loss of Htt function during the murine developmental period leads to motor deficits and hyperkinetic phenotypes expressed during adult life (Arteaga-Bracho et al, 2016). Consistent with our findings, a more recent study reported that deletion of Htt in pallial lineages also results in hyperactivity and motor deficits (Dragatsis et al, 2018). To define whether the selective loss of Htt function in subpallial-derived lineages contribute to HD-like motor abnormalities, we examined motor coordination and free locomotion using the balance beam, rotarod and the open-field tests, respectively.…”
Section: Ablation Of Huntingtin In the Gsx2 And Nkx21 Lineages Resulsupporting
confidence: 92%
“…Therefore, three main aspects of HD pathology, abnormal motor function, reactive gliosis, and SPN death, can be partially produced by Htt loss-of-function in SPNs. Previous studies have shown that loss of Htt in forebrain neurons (Dragatsis et al, 2000) or cortex (Dragatsis et al, 2018) leads to widespread cell death, reduced cortical volume, and abnormal motor behavior. However, the pattern of degeneration does not resemble the striatum-specific SPN loss seen in HD.…”
Section: Loss Of Htt In Spns Partially Recapitulates Several Hdlike Pmentioning
confidence: 99%
“…health and viability, because deleting Htt in the mouse central nervous system leads to aberrant synaptic connectivity, cellular stress, neuroinflammation, and neuronal death (McKinstry et al, 2014;Dragatsis et al, 2000Dragatsis et al, , 2018Mehler et al, 2019). On the other hand, wild-type HTT is neuroprotective and can shield neurons against mHTT toxicity (Leavitt et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Mice deleted for Htt gene, Hdh, die around embryonic day 7.5-10.5, before the full emergence of the nervous system, indicating its role in cell survival and neurogenesis (1)(2)(3)(4). Recent studies found that Htt deletion in the brain of younger mice (two months) led to death due to pancreatitis, and, in the adult brain, there was only a subtle defect in corticostriatal development and hyperactivity (5)(6)(7). The HTT gene, however, does not appear to affect development because HD human patients who are heterozygous or rare cases of homozygous for HTT appear to have normal development (8,9).…”
Section: Introductionmentioning
confidence: 99%